Role of antithyroid autoimmunity as a predictive biomarker of chronic immune thrombocytopenia. Issue 1 (30th September 2018) - Giordano, Paola; Urbano, Flavia; Lassandro, Giuseppe; Bianchi, Francesco Paolo; Tolva, Alessandra; Saracco, Paola; Russo, Giovanna; Notarangelo, Lucia Dora; Gabelli, Maria; Cesaro, Simone; Wasniewska, Malgorzata; Faienza, Maria Felicia
Abstract: Background: Immune thrombocytopenia (ITP) is an acquired immune‐mediated disorder characterized by isolated thrombocytopenia. Pediatric ITP patients are prone to develop autoantibodies such as antithyroglobulin (TG) and antithyroperoxidase (TPO), even in the absence of clinical signs of autoimmune disease. The aim of this multicenter retrospective study was to evaluate (1) the prevalence of positivity of antithyroid antibodies (TPO and TG) in a large cohort of pediatric patients with chronic ITP; (2) the role of autoimmune thyroiditis as a prognostic factor for chronicity of ITP. Procedure: For this retrospective study, we collected data from patients diagnosed as affected by chronic ITP between 2011 and 2014 in six centers belonging to the Italian Association of Pediatric Haematology and Oncology (AIEOP). Results: From the analysis of data, we found a significantly higher prevalence of antithyroid antibodies in children with chronic ITP (11.6%) than in the pediatric population (1.2%–1.3%). No correlation has been found between the platelet count and the prevalence of positive antithyroid antibodies at any detection time of the study. Conclusions: The results of our study demonstrated that (1) the prevalence of positivity for antithyroid antibodies (anti‐TPO and anti‐TG) in pediatric patients with chronic ITP results is significantly higher than in the pediatric population; (2) autoimmune thyroiditis does not seem to play a role as a prognostic factor for chronicity of ITP in pediatric patients.